SOIL MICROBIOLOGICAL ACTIVITY UNDER DIFFERENT TILLAGE METHODS - Hanhur, V.V.; Sakhatska, V.M. (Scientific Progress & Innovations, 2019)
Soybean (Glycine hispida L.) is important in solving the problem of human nutrition and livestock devel-opment, as a valuable food, feed and industrial crop, and also the source of high-grade proteins, vitamins and trace elements. Its cultivation is an important factor in regulating soil biological activity, in particular, microbiological processes, intensity of symbiotic nitrogen fixation on soybean areas. Therefore, it is im-portant to develop technological practices for managing the activity of microbiological processes in the ara-ble soil layer on soybean areas. The purpose of the research was to find out the effect of ordinary plowing, soil loosening with different tillage implements on the activity of cellulose-decomposing bacteria of the plowed soil layer on soybean areas. The following scientific methods were used in the research process: analysis, synthesis, field, and statistical. The results of the conducted researches show that the highest indi-ces of microbiological activity were detected in the soil layer of 20–30 cm – 21.3–22.1 % and the lowest (17.3–19.1 %) – in the layer of 10–20 cm against the background of plowing to the depth of 20–22 cm. It was determined that at loosening the soil with flat type working implements (depth 14–16 cm), as well as at shal-low soil tillage to the depth of 12–14 cm the intensity of linen tissue decomposition was lower than at plow-ing. The research shows that, against the background of basic soil tillage, biological activity decreased in the soil layer from 0–10 cm to 20–30 cm on the average by 9.2 % at flat type tillage and 7.9 % at the mini-mum tillage system. According to the research results, it was established that using different machinery for pre-sowing soil tillage significantly influenced the changing of soil biological activity in the layer of 0-30 cm.It was found that the highest degree of linen fabric decomposition was under pre-sowing soil tillage withAG-4 “Scorpion-1”(20.3 %), and at conducting this technological operation with USMK − 5.4 cultivator,the above mentioned indicator decreased to 19.8 %; at tilling with KPS-4,0 (19.2 %) against the backgroundof plowing with PLN-3-35.